Hypertension and the metabolic syndrome - Smirčić-Duvnjak, Lea (Array, 2008)
Summary: Hypertension is a very common condition which frequently remains undiagnosed until relatively late in its course, leading to a variety of other life-threatening conditions like kidney damage and heart failure. It is a very prominent feature of the metabolic syndrome, present in up to 85% of patients. In the context of global cardiovascular risk, metabolic syndrome is indeed a high risk condition, involving obesity, dyslipidemia, hypertension and diabetes. In spite of controversy surrounding its definition and etiology, metabolic syndrome represents a useful and simple clinical concept which allows for earlier detection of type 2 diabetes and cardiovascular disease.